(untitled) (Scripta : English Department Journal, 2023)
The aim of the study analyzed the effect of using the Spotify Application on EFL students‘ listening achievement of 11th SMAN 4 Sidoarjo. This study used a quantitative method. In data collection, the researcher used the experimental and control group with pre-test and post-test. The population of this research was all the students of SMAN 4 Sidoarjo and the sample of this research was the 11th students of SMAN 4 Sidoarjo who consisted of 33 students. The instrument of this research used to obtain data was listening test. It was used to get data of the student’s listening achievement through English songs by using Spotify Application. The result of the calculation that (the result t-test) was 3,421 in deviation of freedom (df) = 56 by significance standard 5% which was from 2,000. The researcher proved that was higher from . The hypothesis of the research is accepted. Using Spotify Application in teaching listening achievement, and based on average of the student‘s marks, Spotify Application can give the students more experience in listening to foreign language, even only simple sentences at first. The researcher concludes that Spotify Application through English songs is a good application for teaching listening.